Blaschko-Linear Lupus Erythematosus in a Pediatric Patient - Marshall Hall; Olivia Mayer; Henry Lim; Dustin V Wilkes; Michael Carletti; Stephen E Weis (HCA Healthcare Journal of Medicine, 2026)
The lines of Blaschko represent epithelial cell migration during embryonic development. Rare forms of cutaneous lupus erythematosus may manifest along these lines, and lesions are termed Blaschko-linear lupus erythematosus (BLE). The purpose of this case study is to present a rare manifestation of linear cutaneous lupus erythematosus following the lines of Blaschko in a pediatric patient. To date, there are very few reports of BLE. We present a 17-year-old female with a 2-month history of a mildly tender growing lesion along the right nasofacial sulcus. The patient denied lesions elsewhere and any systemic, joint, or mucosal symptoms. A biopsy of the lesion was consistent with cutaneous lupus erythematosus. Given the distribution and pathology, the patient was diagnosed with BLE. The patient was treated with intralesional triamcinolone, topical pimecrolimus, and systemic hydroxychloroquine with an emphasis on strict photo-protection. Despite these therapies the patient’s disease persisted.